Kedudukan Perkara Perdata Sebagai Prajudisial Dalam Proses Pidana: Analisis Terhadap Putusan Mahkamah Agung - Amanda Bherlyana Putri; Gokma Toni Parlindungan S (Universitas Sumatera Barat, 2025)
The relationship between civil cases and criminal cases is often problematic in judicial practice in Indonesia, especially when a criminal case is rooted in a civil conflict such as a dispute over ownership or agreement. In this context, questions arise regarding the position of civil cases as prejudicial, namely to what extent a civil case must be resolved first before a criminal case can be examined. This article aims to analyze the position of civil cases as prejudicial in the criminal process through a normative legal study with a statutory approach and case studies of Supreme Court decisions. The results of the study show that the Supreme Court in several of its decisions recognizes the existence of civil cases as a prejudicial basis that can postpone the criminal process, as long as the main criminal case is closely related to the determination of civil rights that are still in dispute. However, not all civil cases can immediately be used as a reason to suspend the criminal process. Therefore, a careful assessment by law enforcement officers of the substance of the case is needed to ensure legal certainty and protection of the rights of the parties in the judicial process.